Ischnura praematura sp. nov. (Odonata: Zygoptera: Coenagrionidae): a species from Yunnan (China) whose females mate in the teneral state - Sanmartín-Villar, Iago; Lorenzo-Carballa, M. Olalla; Zhang, Haomiao; Cordero-Rivera, Adolfo (Zootaxa, 2022)
Ischnura praematura sp. nov. (Holotype ♂, China, Yunnan, Lijiang, 26º31´03.54”N, 100º13’38.89”E, 2396 m, 04 xii 2015, I. Sanmartín-Villar & H. Zhang leg.) is morphologically described, illustrated and compared with close species of the genus. Ischnura praematura can be mainly distinguished from its congeners I. aurora, I. rubilio and I. asiatica by its abdominal and thoracic morphology and colouration. The posterior lobe of the prothorax is elevated in I. praematura and the mesostigmal plates possess dorsal triangular protuberances. Ischnura praematura shows pointed paraprocts, internalised wide cerci and lacks a dorsal tuberculum in the tenth abdominal segment. The blue abdominal colouration is present in the last three segments (incomplete for segment eight and ten in some individuals). No female polychromatism was detected and all females observed possessed different colouration than male (gynochrome). Morphological distinctiveness of the species is supported by genetic analyses, which show that I. praematura forms a well-supported, monophyletic clade, with I. asiatica, I. ezoin and I. pumilio as the most closely related species. In the field, mature females show strong reluctance to mate, and males were observed mating with newly emerged females.